2021
DOI: 10.3390/diagnostics11091674
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and Progression of Chronic Kidney Disease: A Review from Physiology and Pathogenesis to the Role of Urate-Lowering Therapy

Abstract: The relationship between hyperuricemia, gout, and renal disease has been investigated for several years. From the beginning, kidney disease has been considered a complication of gout; however, the viewpoints changed, claiming that hypertension and elevated uric acid (UA) levels are caused by decreased urate excretion in patients with renal impairment. To date, several examples of evidence support the role of hyperuricemia in cardiovascular or renal diseases. Several mechanisms have been identified that explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 111 publications
0
18
0
1
Order By: Relevance
“…Disturbance of the balance between UA production and excretion would lead to HUA that is considered as an independent risk factor for CKD progression (Johnson et al, 2013). Persistently high-serum UA levels was reported to trigger kidney inflammation and fibrosis that might contribute to HN (Lee et al, 2021). Current standard treatment for HUA is UAlowering drugs represented by XO inhibitors and uricosuric agents, the nephroprotective effect of which remains controversy in CKD patients (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance of the balance between UA production and excretion would lead to HUA that is considered as an independent risk factor for CKD progression (Johnson et al, 2013). Persistently high-serum UA levels was reported to trigger kidney inflammation and fibrosis that might contribute to HN (Lee et al, 2021). Current standard treatment for HUA is UAlowering drugs represented by XO inhibitors and uricosuric agents, the nephroprotective effect of which remains controversy in CKD patients (Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney fibrosis, the ultimate pathological outcome of HN, is characterized by the expression of mesenchymal cell products such as α-SMA, FN, and Col I (Lee et al, 2021). The TGF-β/ Smad3 signaling pathway plays a critical role in mediating profibrotic response of renal epithelial cells and activating renal fibroblasts (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in relation to the cessation of tobacco consumption, there is evidence indicating that it is one of the most effective measures to prevent the progression of renal failure [ 8 , 9 , 41 ]. In a study on patients with diabetic nephropathy, disease progression was observed in 53% of smokers, but only in 33% of former smokers and 11% of non-smokers [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase in XOi use among gouty CKD patients, potential side effects of these medications have become important. This rise in prescription is at least partially contributed to hyperuricemia's suggested role in the progression to end-stage renal disease with studies demonstrating renoprotective potential of XOis (25)(26)(27)(28). Furthermore, hyperuricemia is widely accepted as a risk factor for cardiovascular diseases, perhaps partially due to promotion of chronic formation of neutrophil extracellular traps, thereby contributing to vascular damage (29).…”
Section: Discussionmentioning
confidence: 99%